Adaptive message sending rate control method based on channel congestion cost calculation in VANET - Ming-jian LIU; Guo-zhen TAN; Shuai-bing LI; Nan DING; Cai-xia SONG (Tongxin xuebao)
In VANET,sending beacon messages reliably played a vital role in cooperative awareness and collision avoidance,and changes of vehicle density in real traffic environment had a direct impact on channel load and will cause the channel congestion to a certain degree,thus causing inefficiency of cooperative security applications.Aiming at this issue,a adaptive method based on channel congestion detection to control message sending rate was designed.First of all,an interference model that can accurately reflect the current state of the channel was established.Secondly,according to the Shannon information theory and network utility maximization theory,the optimal transmission speed of the current node in the physical layer was calculated.Finally,according to the mismatch of transmission rate and transmission queue length,the next moment's cost function of the channel congestion degree by monitoring the message queue was established to avoid channel congestion and queue overflow.The simulation experiment shows that the scheme effectively reduces communication transmission delay and avoids channel congestion,ensuring that the data be sent reliably.